Controversial Alkoxyl and Peroxyl Radical Scavenging Activity of the Tryptophan Metabolite 3-Hydroxy-Anthranilic Acid - Lissi-Gervaso, E; Aspee-Lamas, A; Pino-Lopez, E (Elsevier Masson SAS, 2017)
3-Hydroxy-anthranilic acid (3-OHAA), a tryptophan metabolite produced in the kynurenine pathway, is an efficient antioxidant towards peroxyl radicals (ROO[rad]) derived from the AAPH (2,2′-azobis(2-amidinopropane) dihydrochloride) thermolysis. However, self-reactions of ROO[rad] can give rise to alkoxyl radicals (RO[rad]), which could strongly affect the fate of scavenging reactions. In the present work, we studied the influence of RO[rad] in the scavenging activity of 3-OHAA in three different systemsi) Monitoring of the direct reaction between 3-OHAA and AAPH-derived free radicals (kinetic studies); ii) Evaluation of the protective effect of 3-OHAA on the AAPH-induced consumption of fluorescein; and, iii) Inhibition, given by 3-OHAA, of the AAPH-initiated lipid peroxidation of both, rat brain synaptosomes and homogenate preparations (assessed by chemiluminescence). For such purposes, the fraction of free radicals (f) trapped per 3-OHAA molecule was determined in each system. Kinetic results show that the oxidation of 3-OHAA follows a process dominated by ROO[rad] with a zero order kinetic limit in 3-OHAA, and a fraction (fri) equal to 0.88. From the induction times, elicited by 3-OHAA in the kinetic profiles of fluorescein consumption, a fraction (fT) of 0.28 was determined. 3-OHAA also generated induction times in the kinetic profiles of light emission during the AAPH-initiated lipid peroxidation of rat brain synaptosomes and homogenates. From such induction times, fractions of 0.61 and 0.63 were determined for rat brain synaptosomes (fsyn) and homogenates (fhom), respectively. These results show that during the incubation of 3-OHAA and AAPH, a low fraction of ROO[rad] self-reacts to generate RO[rad]. Nevertheless, when 3-OHAA is employed to protect particular targets, such as fluorescein, rat brain synaptosomes and homogenates, reactions of ROO[rad] and/or RO[rad] should be considered. © 2017 Elsevier Masson SAS